Relation between iodine nutrition and thyroid diseases in Qinghai, China - Fan, Xiaoxia; Zhao, Lingling; Wang, Shuqiong; Song, Kang; Wang, Beibei; Xie, Yanling; Jiang, Yanping; Lin, Lijun; Teng, Weiping; Cai, Chunmei; Yao, Yongli (Frontiers in Endocrinology, 2023)
Objective To investigate the adult iodine nutrition and the prevalence of thyroid diseases in Qinghai Province, and analyze the correlation between iodine and thyroid diseases, so as to provide a basis for adjusting the salt iodization plan in Qinghai Province. Methods Using cluster and stratified sampling method to select 2628 permanent residents over 18 years old in Qinghai Province for questionnaire survey, physical examination, thyroid color ultrasound, and laboratory index detection. Results 1. The coverage of iodized salt in adults is 99.71%. 2. The detection rates of thyroid disorders in adults were as follows: Clinical hyperthyroidism was 1.20%, subclinical hyperthyroidism was 0.20%, clinical hypothyroidism was 1.00%, subclinical hypothyroidism was 29.20%, and the goiter was 2.10%. The percentages positivity of TPO Ab, TG Ab, goiter was 9.80%, 9.20%, 2.10%, respectively. Among them single thyroid nodule was 6.40%, multi-nodule thyroid gland was 1.80%. 3. The percentages of mild iodine deficiency, moderate iodine deficiency, Severe iodine deficiency, adequate iodine intake (AI), more than adequate iodine intake (MAI)and excessive iodine intake (EI)were 8.41%, 2.17%, 0.26%, 33.22%, 28.35%, and 27.59%, respectively. The percentages of mild, moderate and severe iodine deficiency in urban populations (7.13%, 0.87%, 0.0%) were significantly lower than those in rural populations (9.81%, 3.59%, 0.56%) (P < 0.05), and the rates of adequate, more than adequate iodine intake in urban populations (36.03%, 30.93%) were significantly higher than that in rural populations (30.14%, 25.52%). The rate of excess iodine intake was higher in rural areas (30.38%) than in urban areas (25.04%). 4. The positive rates of subclinical hypothyroidism, goiter, TPO Ab and TG Ab in female adults (35.28%, 3.39%, 13.54%, 13.94%) were higher than those in male adults (23.58%, 0.96%, 6.266%, 4.79%). The detection rate of single thyroid nodules was higher in urban (8.01%) than rural populations (4.70%), while the detection rate of hypothyroidism, subclinical hypothyroidism, and goiter (0.58%, 25.84%, 1.38%) was lower than that in rural populations (1.52%, 32.96%, 2.96%) (P<0.05). 5. There was no statistical significance in the detection rates of clinical hyperthyroidism, subclinical hypothyroidism, subclinical hypothyroidism, goiter, thyroid nodules, TPO Ab and TG Ab positive rates in different iodine nutritional status (P>0.05). The positive rate of hypothyroidism in the iodine deficiency group is higher than in other iodine nutrition groups. Conclusion The nutritional status of iodine in Qinghai Province is iodine excess. Subclinical hypothyroidism was detected at a high rate. Subclinical hypothyroidism, goiter, TPO Ab, and TG Ab were more common in female than in male. The proportion of mild, moderate, and severe iodine deficiency was higher in urban areas than in rural areas. The detection rate of thyroid nodules was higher in urban than in rural areas, and that of hypothyroidism, subclinical hypothyroidism, and goiter was lower than that in rural populations. The detection rate of clinical hypothyroidism was statistically significant in different iodine nutritional states (P< 0.05).